Trip generation trip generation rates, plots, and equations. - Institute of Transportation Engineers (Washington, DC Institute of Transportation Engineers, 1997)
The sixth edition of Trip generation includes several significant changes in format and content as compared to the fifth edition. To facilitate use of the document, the overall publication has been repackaged into three volumes: Volumes 1 and 2, containing land use descriptions and data plots, and a User's guide, containing the general introductory, instructional and appendix material. A significant amount of new data has been collected since the publication of the fifth edition. Data from more than 750 new studies have been added to the existing database for a combined total of more than 3,750 individual trip generation studies.
Includes bibliographical references (v. 3, p. 29-39) and index.
Keywords: Trip generation -- United States; Traffic surveys -- United States; Transportation -- Planning -- Statistical methods; Traffic estimation -- United States -- Mathematical models